Modified space vector pwm transformerless inverters with reduced common mode voltage and leakage current / Freddy Tan Kheng Suan - Freddy Tan, Kheng Suan (2015)
Small, highly efficient and low cost photovoltaic (PV) system can be achieved when the transformer is removed from the PV inverter. Nevertheless, transformerless PV inverters generates dangerous leakage currents. Therefore, various transformerless PV inverters topologies are proposed recently to reduce the leakage current to meet the requirement of the standard. In this project, two types of recently proposed transformerless PV inverters are investigated, i.e., single-phase and three-phase inverters. A common-mode model circuit for each type is developed to study the common-mode behavior of the transformerless PV inverters. It is shown that the leakage current is directly depending on the common-mode voltage (CMV). Based on the analysis of the studies, a novel transformerless PV inverter topology is proposed for both single-phase and three-phase PV systems respectively. For single-phase PV systems, a simple modified H-bridge zero-voltage state rectifier (HBZVR-D) is proposed to eliminate the leakage current. A fast-recovery diode is added to the existing HBZVR topology to improve the clamping branch performance. It is shown that the improved clamping branch of the proposed topology completely clamps the CMV to constant to eliminate the leakage current. On the other hand, a three-phase transformerless inverter (H7), adapted from the single-phase H5 topology, is investigated. An additional switch is added to the conventional full-bridge structure to provide galvanic isolation. Here, a novel modulation technique based on conventional discontinuous pulsewidth modulation is proposed. It is shown that the proposed topology is able to reduce the CMV in order to reduce the leakage current. The validity of the proposed inverters are verified via simulations and laboratory prototypes. DSP TMS320F28335 is used to program the modulation techniques. The performances of the proposed topologies, in terms of CMV, leakage current, total harmonic distortion (THD) and efficiency, are compared with various recently proposed transformerless PV inverters. It is experimentally proven that the proposed transformerless single- and three-phase inverters are able to reduce the leakage current with superior overall performance among the recently proposed topologies.